2020
DOI: 10.1021/acs.energyfuels.9b04122
|View full text |Cite
|
Sign up to set email alerts
|

Study of Shale Gas Release from Freshly Drilled Core Samples Using a Real-Time Canister Monitoring Technique: Release Kinetics, Influencing Factors, and Upscaling

Abstract: Gas release from organic-rich shale rock plays a significant role in the migration and production of hydrocarbons in the shale reservoir. Despite recent progress in gas adsorption/desorption experiments and molecular simulation, information on the actual gas release process remains stagnated. Here, we demonstrate the real-time canister monitoring technique as a powerful tool to investigate the kinetics of shale gas release from freshly drilled core samples. Combined with the adsorption capacity measurement, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…With regard to this, a gas release measurement technique called wellsite canister testing has been adopted to measure the shale gas content and compo-sitions (e.g., methane, ethane, nitrogen, carbon dioxide, and hydrogen) in recent years [10][11][12][13][14]. Here, we use the term "gas release" instead of "gas desorption," and the main reason is that gas production from shale is the outcome of several different types of gas release process, including, but not limited to, desorption, and the gas release process should in fact be referred to "release" in order to encompass all forms of gas release process during canister testing [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to this, a gas release measurement technique called wellsite canister testing has been adopted to measure the shale gas content and compo-sitions (e.g., methane, ethane, nitrogen, carbon dioxide, and hydrogen) in recent years [10][11][12][13][14]. Here, we use the term "gas release" instead of "gas desorption," and the main reason is that gas production from shale is the outcome of several different types of gas release process, including, but not limited to, desorption, and the gas release process should in fact be referred to "release" in order to encompass all forms of gas release process during canister testing [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the focus of the in situ gas desorption test is to obtain the content, composition, and geochemical characteristics of desorbed gas so as to determine the occurrence state and origin of desorbed gas. , However, the variation characteristics of the in situ gas desorption curve itself and its geological significance have not attracted enough attention. Different shale gas desorption behaviors have been found in studies of Dang et al on the Shan Formation and Taiyuan Formation shales and Tang et al on the Shuijingtuo Formation shales, but the reasons for this were not explored.…”
Section: Introductionmentioning
confidence: 99%
“…Dang et al [11] compared different methods for "lost" gas estimation based on a shale gas play in China. Nie et al [12] demonstrated that time-series desorption data of freshly drilled cores can provide valuable information regarding the kinetics of gas release from shale cores.…”
Section: Introductionmentioning
confidence: 99%